Implementation of IoT-Based Hydroponic Farming to Enhance Production Capacity and Management of Farmer Groups in Probolinggo Regency - Tjahjaningsih, Yustina Suhandini; Mimik Umi Zuhroh; Andrik Sunyoto; Ira Aprilia (Edumedia Solution, 2025)
This community engagement program aimed to enhance agricultural productivity and management capacity of two farmer groups in Probolinggo Regency—Poktan Karya Luhur II and Poktan Gebangan Makmur—through the adoption of IoT-based hydroponic farming. Activities included designing and installing deep water culture (DWC) and nutrient film technique (NFT) systems with sensors for pH, EC/TDS, temperature, and humidity; training on hydroponic cultivation and food safety; and workshops on bookkeeping and financial literacy. The results showed that farmers could operate the systems independently, monitor crop conditions in real time, and reduce water and nutrient waste. Production cycles became more stable compared to conventional farming, while managerial capacity improved through better record-keeping and cost analysis. Overall, the program increased productivity, efficiency, and farmer self-confidence, demonstrating that sustainable community empowerment requires both technological innovation and organizational strengthening